(untitled) (Research, Society and Development, 2021)
This article is a descriptive-exploratory study of the experience report type and aims to present the results obtained in the workshop: “Origami, Geometry and Fun”, held at the VIII Dialogues of Mathematics with Pedagogy (DIMA). The methodological procedure of this workshop was based on the assumptions of the Fedathi Sequence (SF) methodology, based on its phases: Position taking, Maturation, Solution and Proof; and it took place through research in the classroom, using the observation of subjects and the application of an evaluative questionnaire as data collection techniques. As main results, it was observed that in the Taking of Position, with the proposed problem-situation, the participants, mainly students of the Pedagogy Course of the Faculty of Education of the Federal University of Ceará, had difficulties in identifying the geometric concepts in the Origami and that in the Proof phase, it was found that the making of cube-shaped origami was crucial for the understanding of the geometric concepts worked. It appeared that the objective of the workshop was achieved, considering that the participants understood the relationship between the forms produced in Origami and the teaching of Geometry, in addition, they felt interested in using this technique during their practices in classroom.